Establishment Of Cell Suspension Culture Of Hyoscyamus Niger L. For The Production Of Tropane Alkaloids - Ishak, Rafidah (2012)
Aseptic seeds of Hyoscyamus niger were established via two-stage surface sterilization protocol using Clorox® solution coupled with Teepol with 95.6% of the seeds were aseptic. From these aseptic seeds, 79.8% of the seeds germinated and 100% of the seed-derived plantlets survived. Callus could be induced from the leaf, petiole and root explants of the in vitro plantlets on MS medium supplemented with 2.0 - 10.0 mg/L picloram. The leaf explants inoculated to MS medium supplemented with 2.0 mg/L picloram produced the best callus for cell suspension cultures.